TiB₂/GaAs and Au-TiB₂/GaAs structural transformations at short-term thermal treatment - Kryshtab, T.G.; Lytvyn, P.M.; Mazin, M.O.; Lytvyn, O.S.; Prokopenko, I.V.; Ivanov, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The investigations of TiB₂/GaAs and Au-TiB₂/GaAs structural characteristics in dependence on technological regimes of sputtering and TiB2-film thicknesses as well as structural relaxation processes at short-term thermal annealing were carried out. TiB₂-film on Czochralski-grown (001) GaAs substrates were prepared by the magnetron sputtering in argon atmosphere at growth velocity ~ 5 Е/s and film thicknesses ranging from 10 to 50 nm. Samples were annealed during 1 min at 400, 600 and 800 °C. By using X-ray diffraction methods, it was shown that at our experimental conditions the magnetron sputtering of titanium diboride film causes the titanium and boron solid solutions formation as well as formation of some other phases within an interface region. At short-term thermal annealing the relaxation of mechanical strains, decay of solid solutions, generation of dislocations and their propagation as well as point defects redistribution take place. The processes of structural ordering have non-monotonous temperature dependence and differ for various types of structures.